Effect of Temperature and Storage Time on The Quality of Quail Egg (Coturnix coturnix japonica) - Siti Rani Ayuti; Monita Previa Alasa; Rastina Rastina; Hennivanda Hennivanda; Muhammad Hambal; Abbas Abbas (Universitas Syiah Kuala, 2021)
Many people favor quail eggs because they contain good nutrients, and are easy to obtain at an affordable price. This research was conducted to study the effect of temperature and storage time on the quality of quail eggs. The samples in this study were 66 quail eggs which were divided into two groups, the first group (33 eggs) was stored at 27oC, and the second group (33 eggs) was kept at 5oC. This study used a completely randomized design with two factors, temperature and storage time. The observation was carried out on days 1, 7, 13, 19, 25, and 31 with triplicates. The parameters used in this study were air sac height, egg yolk index, white egg index, and Haugh Unit (HU). This study showed that temperature and storage time affected the quality of quail eggs. Eggs stored at 27oC showed a quality decrease indicated by higher air sac position, and lower egg yolk index and egg white index. Eggs kept at 5oC showed no significant degradation. The HU for both groups ranged between 76-81 which implied that the eggs had AA quality even after 31 days of storage.